Random amplified polymorphic DNA profiles as a tool for the characterization of Brazilian keratitis isolates of the genus Acanthamoeba - Alves,J.M.P. (2000)
The genus Acanthamoeba comprises free-living amebae identified as opportunistic pathogens of humans and other animal species. Morphological, biochemical and molecular approaches have shown wide genetic diversity within the genus. In an attempt to determine the genetic relatedness among isolates of Acanthamoeba we analyzed randomly amplified polymorphic DNA (RAPD) profiles of 11 Brazilian isolates from cases of human keratitis and 8 American type culture collection (ATCC) reference strains. We found that ATCC strains belonging to the same species present polymorphic RAPD profiles whereas strains of different species show very similar profiles. Although most Brazilian isolates could not be assigned with certainty to any of the reference species, they could be clustered according to pattern similarities. The results show that RAPD analysis is a useful tool for the rapid characterization of new isolates and the assessment of genetic relatedness of Acanthamoeba spp. A comparison between RAPD analyses and morphological characteristics of cyst stages is also discussed.